2009
DOI: 10.1007/s00432-009-0588-2
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of hepatectomy with adjuvant transcatheter arterial chemoembolization versus hepatectomy alone for Stage III A hepatocellular carcinoma

Abstract: For Stage IIIA HCC, hepatectomy with adjuvant TACE efficaciously and safely improved survival outcomes when compared with hepatectomy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 37 publications
6
108
0
Order By: Relevance
“…Several studies showed better survival [7]. The benefit of TACE as adjuvant treatment is controversial [19,20], and several studies report only a limited benefit in patients with advanced HCC of large size or with vascular invasion [21][22][23]. Further, one study reported that TACE performed after confirmation of recurrence was more effective compared to TACE performed regularly, irrespective of the evidence of tumor recurrence [24].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies showed better survival [7]. The benefit of TACE as adjuvant treatment is controversial [19,20], and several studies report only a limited benefit in patients with advanced HCC of large size or with vascular invasion [21][22][23]. Further, one study reported that TACE performed after confirmation of recurrence was more effective compared to TACE performed regularly, irrespective of the evidence of tumor recurrence [24].…”
Section: Discussionmentioning
confidence: 95%
“…For patients with BCLC stage B HCC, TACE is clearly defined as the first-line therapy and hepatic resection is not considered as a suitable method because of the high risk of hepatic decompensation after surgical resection. However, the results of a meta-analysis and some studies revealed that hepatectomy plus adjuvant TACE was superior to hepatectomy alone in patients with HCC with less incidence of tumor recurrence and mortality [21,24,35]. In the present study, our results showed that treatment modalities were an independent prognostic factor of overall survival rates by the Cox regression model (P = 0.033) and suggested that postoperative adjuvant TACE could improve the survival of patients with HBV-related HCC (stage B) compared to surgery only.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that Asp and Glu have synergistic effects on tumor suppression. Recent studies indicated that a functional N-methyl-D-aspartate receptor (NMDAR) was expressed in HepG2 and Huh-7 cells (20), and NMDAR-dependent signaling would be related with cancer cell growth (10,18,31). Therefore, Asp and Glu may function through NMDAR to inhibit tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%